Alcohol use and associated factors among high school, college and university students in Ethiopia, systematic review, and meta-analysis, 2018. (3rd July 2020) - Amare, Tadele; Getinet, Wondale
Abstract: Background: Alcohol is a psychoactive substance that is widely consumed in the world. Alcohol use is the most prevalent among early adulthood. It affects individuals' mental, physical, economical and their social issues. Aim: To show prevalence of alcohol use and associated factors among students in Ethiopia by reviewing relevant literature. Methods : Systematic review and meta-analysis of published studies on the prevalence of alcohol use and associated factors among students in Ethiopia were conducted. Data were searched using PubMed/Medline, Global Health, Africa-wides, PsycINFO, Google Scholar and EMBASE databases. We used the preferred reporting items for systematic reviews and meta-analyses statement for reporting. The prevalence of alcohol use and associated factors was approved using the random-effects model and measured as the proportion of alcohol use (with 95% CI). Result: A month-pooled estimated prevalence of alcohol use among university, college and high school students was 26.19%. University, college and high school students who had used alcohol in the last 1-month were 25.27%, 32.34% and 23.44% respectively. Factors like being male, peer pressure and living alone were associated factors for alcohol use. Conclusion: Alcohol use among students was higher than the general population. It is better to give special attention to school students.